Mastering jQuery : elevate your development skills by leveraging every available ounce of jQuery - Libby, Alex (Community experience distilled., 2015)
If you are a developer who is already familiar with using jQuery and wants to push your skill set further, then this book is for you. The book assumes an intermediate knowledge level of jQuery, JavaScript, HTML5, and CSS.